PROMOTING OPEN SCIENCE WITH INSTITUTIONAL REPOSITORIES IN THE MALAYSIAN COMPREHENSIVE PUBLIC UNIVERSITIES - Ahmed, Mahfooz; Othman , Roslina (Journal of Information Systems and Digital Technologies, 2021)
This study examines the level of openness of the intellectual collections in the Malaysian Public Universities Repositories, towards promoting the practice of open science in the institutions. Open science stands for a new system in which researchers all over the globe can come together and contribute to all research processes and at the end of the processes allows for the sharing of the scientific findings that are beneficial to all humanities freely. Specifically, the main objectives of the study were to identify, to what extent were the intellectual contents in the Institutional Repositories (IR) of the comprehensive universities in Malaysia open to the general public and how the librarians and researchers from these universities promote open science through the IR. Mixed-method research was used to gather information from the respondents. A total of 255 responses were received for the quantitative method and a total of 6 librarians were interviewed for the qualitative method to complement the other and triangulation was done to aggregate the major findings, which shows that the public universities in Malaysia were involved in OS through their institutional repositories. However, only 10% to 30% of the contents in these IR were available to the general public, while some institutions only provide the abstract to the public. Some recommended factors identified by the stakeholders to fully implement the OS practices were: the need for more enlightenment on the system, more of the modern digital facilities or infrastructure such as high-speed internet, and well-managed and secured databases.